2006
DOI: 10.1002/mabi.200690012
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Macromol. Biosci. 7/2006

Abstract: Cover: The picture depicts a versatile, goldbased platform developed to optimize nanoparticle properties. Nanoparticles with optimal size, hydrophilicity and ligand display successfully target hepatocytes. The design properties determined by this method can be applied to develop targeted nanoparticulate drug carriers. Further details can be found in the article by J. M. Bergen, H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 0 publications
2
42
0
Order By: Relevance
“…It also implicated that ICG molecules were wellprotected by MSN-TA for in vivo imaging, and the confined space of MSN-TA might impede ICG being metabolized by enzymes presence in liver. Liver accumulation was also observed in the previous works on other types of nanoparticles (i.e., liposomes, [37] chitosan, [38] magnetite, [39] gold nanoparticles, [40] and carbon nanotubes [41] ). A preliminary validation of the noninvasive imaging capability of MSN-TA-ICG was performed by imaging its biodistribution in anesthetized nude mice.…”
Section: Full Papermentioning
confidence: 52%
“…It also implicated that ICG molecules were wellprotected by MSN-TA for in vivo imaging, and the confined space of MSN-TA might impede ICG being metabolized by enzymes presence in liver. Liver accumulation was also observed in the previous works on other types of nanoparticles (i.e., liposomes, [37] chitosan, [38] magnetite, [39] gold nanoparticles, [40] and carbon nanotubes [41] ). A preliminary validation of the noninvasive imaging capability of MSN-TA-ICG was performed by imaging its biodistribution in anesthetized nude mice.…”
Section: Full Papermentioning
confidence: 52%
“…The mentioned applications often call for monodisperse nanoparticles of a particular size in large quantities and/or at high concentrations [19,20]. Therefore, it is important to understand how changes in the synthesis conditions can affect the nanoparticle characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Galactose-PEG-thiol ligand on AuNPs effectively resulted in hepatocyte targeted delivery in vivo. 5 The influence of anchoring ligands and particle size on the colloidal stability of PEG-coated AuNPs has also been reported. 6 This study suggests that AuNPs (20 nm) coated with thioctic acidterminated PEG (MW 5,000) are promising for potential drug delivery vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…4 Bergen et al reported that the modification of AuNPs surface with PEG-thiol or galactose-PEG-thiol afforded steric stabilization at physiological salt concentrations under conditions where unmodified AuNPs aggregated. 5 In addition, PEG modification does not significantly affect the surface charge and size of AuNPs. Galactose-PEG-thiol ligand on AuNPs effectively resulted in hepatocyte targeted delivery in vivo.…”
Section: Introductionmentioning
confidence: 99%